A Comparative Study of Indonesia and Malaysia's Economic Resilience in the COVID-19 Era: An Analysis of Economic Stability - Al Waroi, Muhammad Nur Abdul Latif Nur Latif (UI Scholars Hub, 2024)
This study analyzes the economic resilience of Indonesia and Malaysia during the COVID-19 pandemic, focusing on economic stability. The research explores pre-pandemic economic conditions, the impact of COVID-19 on GDP, inflation, unemployment, and government debt, as well as recovery efforts through fiscal and monetary policies. Data from Statistics Indonesia, Department of Statistics Malaysia, World Bank, and IMF were used. Results indicate that Indonesia experienced a faster economic recovery, with GDP growth returning to pre-pandemic levels quicker than Malaysia. The economic impact of the pandemic in Indonesia is lower, supported by the National Economic Recovery Program (PEN) and Bank Indonesia's monetary policy. Malaysia experienced a slower recovery despite fiscal stimulus and monetary intervention from Bank Negara Malaysia. The findings show Indonesia has better economic resilience with a quick recovery on key economic indicators, providing important lessons for policymakers. Economic diversification, efficient government spending, sustainable debt management, flexible monetary policy, and appropriate fiscal policy are key to economic resilience and stability. Future research can focus on the long-term impact of COVID-19 on economic structure and labor market to improve the understanding of economic resilience.